SUMBER HAK MILIK DALAM PERSPEKTIF HUKUM ISLAM - ., Yusdani (Al-Mawarid Jurnal Hukum Islam, 2003)
The following article describes the source of ownership in Islamic law viewpoint. The basic concept of ownership in Islamic law perspective has a particular concept if it compares with that of Civil Law, Capitalism and Socialism, especially in terms of the source of ownership. The writer of the article declares that the sources of ownership in Islamic viewpoint are ihram al-megawatt, ad, khalafiyat, and tawallud min mamluk. The concept of aqd or transaction as a source of ownership in Islamic social law, muslims should develop the new kinds of aqd in accord with the free of the contract principle in Islamic law. To develop the new kinds of aqd in Islamic law is so important in the context of response the development of the modern social matters.